Implementation of School-Based Management - Rian Sigit Gesang Permana; Siti Zahrotun Rodiah (Sekolah Tinggi Agama Islam Ma`arif Kalirejo Lampung Tengah, 2022)
School-based management is an effort to increase educational creativity. The purpose of this study was to determine the process of planning, implementation, community participation, and supporting factors in the implementation of school-based management. This research use desciptive qualitative approach. Data collection methods are observation, interviews, and documentation. The subjects of this study were the principals and teachers of MTs Islamiyah Sukoharjo. The results showed that the planning process in implementing school-based management involves decisions, vision, mission and goals that are achieved by assessing the strengths, obstacles, opportunities and challenges faced by MTs Islamiyah Sukoharjo. Implementation of school-based management at MTs Islamiyah Sukoharjo by involving the School Committee, RKAM has been made, School Committee participation, and curriculum adjustments. Community participation or school committees have obligations and functions to improve the quality of education in educational units. The school committee supports, provides, motivates, and monitors teacher performance and establishes partnerships with other parties in seeking funding and extracurricular activities. Factors that support and hinder the implementation of school-based management at MTs Islamiyah Sukoharjo. School residents, student guardians, and school committees support the progress of the school. This is evidenced by the school committee who always participates in supporting school programs, and school residents and school committees are always involved in the preparation and implementation of school programs.